Autonomy and the Patient with Right Hemisphere Cognitive-Communication Deficits: Ethical Considerations in Rehabilitation Practice - Cherney, Leora R.; Kinsey, Laura; Larkin Conlon, Elissa (Seminars in Speech and Language, 2020)
Clinicians must often contend with ethical issues that arise during rehabilitation. When a patient has right hemisphere damage (RHD), these concerns may be exacerbated because of the presence of cognitive deficits. In this article, we focus on the ethical principle of respect for autonomy, which raises issues relevant to patients with RHD who have impaired executive control functions. Respect for autonomy involves respecting others in terms of their decision-making and subsequent actions. Disagreements may occur between members of the rehabilitation team, the patient, and family about the decisions that the patient makes. Clinicians may have concerns about the patient's capacity to make informed decisions. Indeed, in some cases, because the patient is “talking,” the verbal skills may mask the impairments in underlying cognitive processes. We provide two case examples of patients with RHD with sufficient language skills to express their choices, but cognitive deficits that affect their decision-making abilities. We use a clinical decision-making model adapted from Jonsen et al to discuss the cases. In both cases, the rehabilitation team strives to balance what they deem to be in the best interest of the patient while continuing to respect the patient's autonomy.
Keywords: autonomy; right hemisphere stroke; executive function; decisional capacity; cognition